Rapid and Selective Absorption of Plant Defense Compounds From the Gut of a Sequestering Insect - Yang, Zhi-Ling; Seitz, Fabian; Grabe, Veit; Nietzsche, Sandor; Richter, Adrian; Reichelt, Michael; Beutel, Rolf; Beran, Franziska (Frontiers in Physiology, 2022)
Many herbivorous insects exploit defense compounds produced by their host plants for protection against predators. Ingested plant defense compounds are absorbed via the gut epithelium and stored in the body, a physiological process that is currently not well understood. Here, we investigated the absorption of plant defense compounds from the gut in the horseradish flea beetle, Phyllotreta armoraciae, a specialist herbivore known to selectively sequester glucosinolates from its brassicaceous host plants. Feeding experiments using a mixture of glucosinolates and other glucosides not found in the host plants showed a rapid and selective uptake of glucosinolates in adult beetles. In addition, we provide evidence that this uptake mainly takes place in the foregut, whereas the endodermal midgut is the normal region of absorption. Absorption via the foregut epithelium is surprising as the apical membrane is covered by a chitinous intima. However, we could show that this cuticular layer differs in its structure and overall thickness between P. armoraciae and a non-sequestering leaf beetle. In P. armoraciae, we observed a thinner cuticle with a less dense chitinous matrix, which might facilitate glucosinolate absorption. Our results show that a selective and rapid uptake of glucosinolates from the anterior region of the gut contributes to the selective sequestration of glucosinolates in P. armoraciae.